Comparison of safety and efficacy of triamcinolone 40 mg/ml with 10 mg/ml in chalazion - Ali, Araf; Sajjad, Sheikh (International Journal of Research in Medical Sciences, 2023)
Background: Chalazion is a chronic sterile lipogranuloma caused by the obstruction and inflammation of the sebaceous glands of eyelids. A deep chalazion is caused by inflammation of the tarsal meibomian glands and a superficial chalazion by inflammation of Zeis glands. The main objective of the study was to compare the efficacy and safety of intralesional triamcinolone acetonide of 40mg/ml with 10mg/ml in patients with chalazion. Methods: A comparative study was conducted at SKIMS MCH from January 2020 to August 2021. 68 patients were randomly divided into group A and group B. There were 32 eyes with chalazion in Group A and 36 eyes with chalazion in Group B. Group A was treated with triamcinolone 40mg/ml and group B with 20mg/ml. The follow-up was done at 1 week, 4 weeks, and 6 weeks. Results: Of 32 eyes in Group A complete resolution was seen in 28 eyes (87.5%). In Group B out of 36 eyes, complete resolution was seen in 24 eyes (66.6%). Out of 68 patients, 30 were males (44.2%), and 38 were females (55.8%). Complications were marginally more in Group A, 3 patients had yellow white deposits on eyelids and 2 patients had raised intraocular pressure post steroid injection. In Group B, only 2 patients had yellow white deposits on eyelids. The size of the chalazion ranges between 5 to 12 mm. Complete resolution is considered when size reduction >85-90%. Conclusions: It is concluded that intralesional triamcinolone acetonide of 40mg/ml is more effective than 10mg/ml. Although complications are slightly more in the previous than later, it is the rise in intraocular pressure which is of more concern. Thus proper pre-op workup and monitoring of intraocular pressure in the follow-up period are required.